Do the Average Level and Dispersion of Socio-Economic Background Measures Explain France's Gap in PISA Scores? - Boulhol, Hervé (OECD Publishing, 2013)
OECD's PISA publications highlight the impact of economic, social and cultural status (ESCS) on students' results within countries. The focus here is to investigate whether ESCS measures could contribute to differences in aggregate educational outcomes between countries. There is some evidence that, after controlling for education spending and the overall level of economic development, differences in ESCS might account for a substantial amount of France's gap in average PISA scores with respect to best performing OECD countries, albeit by no means all of it
Keywords: Education; Economics; France